Fear of dementia in adults without diagnosed dementia: an updated systematic review of prevalence, measurement, and correlates - Feng Chen; Sixian Li; Kuai In Tam; Huimin Su (Frontiers in Public Health, 2026)
Background Dementia is a major public health concern. Adults, particularly older adults may experience fear of dementia due to concerns about current and future cognitive decline, loss of independence, or increased burden on their families. Previous reviews have mainly focused on concepts, measurement, or assessment tools. Therefore, it is necessary to summarize current evidence on fear of dementia among adults without a diagnosis of dementia. Objective To primarily synthesize the reported prevalence or levels, measurement approaches, and associated factors of fear of dementia among adults without diagnosed dementia, and secondarily explore cultural patterns across Chinese/East Asian and Western contexts. Methods Following PRISMA 2020 guidelines, eight Chinese and English databases were searched from inception to April 10, 2026. Study quality was assessed using JBI tools, and measurement properties were evaluated according to the COSMIN framework. Results 56 studies met the inclusion criteria. Study populations included adults aged 18 years or older, including university students, general adult populations, older adults living in the community, hospitalized older patients, and residents of long-term care facilities. Most standardized instruments demonstrated good internal consistency and structural validity; however, evidence remained insufficient regarding content validity, cross-cultural equivalence, measurement error, and responsiveness. Female, subjective memory complaints, depression, anxiety, negative attitudes toward aging, perceived personal risk of dementia, and a family history of dementia or previous contact with dementia were associated with higher levels of fear of dementia, whereas social support and favorable family functioning were associated with lower levels. The available evidence suggested that Western studies more often emphasized on the loss of autonomy, disruption of self-identity, and diminished perceived personal control, whereas patterns reported primarily in Chinese studies emphasized family burden, intergenerational responsibility, filial piety, and stigma. Evidence from other East Asian settings was insufficient to establish a broader regional pattern. Conclusion Fear of dementia and related constructs were frequently reported across the included studies, although their prevalence and magnitude could not be estimated reliably because of substantial methodological and measurement heterogeneity. Future research should investigate whether incorporating its assessment into community-based cognitive health programs improves engagement, timely help-seeking, or psychological outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero/#searchadvanced , CRD420261419549.